2009
DOI: 10.1096/fj.08-123877
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of tau induced in neurites by microglial proinflammatory mediators

Abstract: Aggregated fibrillary microtubule-associated protein tau is the major component of neurofibrillary tangles in Alzheimer's disease. The exact molecular mechanism of tau aggregation is unknown. Microglial cell activation and migration toward amyloid-beta plaques precede the appearance of dysmorphic neurites and formation of neurofibrillary tangles. Here, we analyzed the accumulation of tau at a distance range of expected spontaneous aggregation by fluorescence lifetime-based Förster resonance energy transfer in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
107
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(117 citation statements)
references
References 56 publications
6
107
0
4
Order By: Relevance
“…[88][89][90] Similarly, a recent study showed that induced airway allergy in mice modified the brain inflammatory status and increased phosphorylation of tau. 91 Given that phosphorylation of tau is crucial for regulation of microtubule stability and axonal transport, 92 and that hyperphosphorylated tau not only affects the microtubule network but also induces accumulation of filamentous actin and formation of actin-rich rods, 93 these observations could provide a link between inflammatory processes and cytoskeletal abnormalities observed in postmortem examination of all AD cases.…”
Section: Early Cytoskeletal Impairmentsmentioning
confidence: 93%
“…[88][89][90] Similarly, a recent study showed that induced airway allergy in mice modified the brain inflammatory status and increased phosphorylation of tau. 91 Given that phosphorylation of tau is crucial for regulation of microtubule stability and axonal transport, 92 and that hyperphosphorylated tau not only affects the microtubule network but also induces accumulation of filamentous actin and formation of actin-rich rods, 93 these observations could provide a link between inflammatory processes and cytoskeletal abnormalities observed in postmortem examination of all AD cases.…”
Section: Early Cytoskeletal Impairmentsmentioning
confidence: 93%
“…Primary microglia and neuronal cells were prepared as described previously (Takahashi et al, 2005;Gorlovoy et al, 2009). Cells were either untreated or treated with 0.5 U/ml endo-N-acetylneuraminidase (EndoN) for 5 h to remove PSA.…”
Section: Methodsmentioning
confidence: 99%
“…Several mechanisms can be envisaged for this release and re-uptake (e.g., via exosomes; Aguzzi and Rajendran 2009). Alternatively, affected neurons could release factors (e.g., cytokines) that then challenge other neurons, either directly or via intermediate cells; an example is the cytosolic accumulation of Tau in neurons encountering activated microglia or exposed to tumor necrosis factor a (Gorlovoy et al 2009). …”
Section: Tau Protein In Neurofibrillary Degenerationmentioning
confidence: 99%